2018
DOI: 10.1089/vbz.2017.2246
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Orientia tsutsugamushi, the Etiological Agent of Scrub Typhus in Animal Hosts and Mite Vectors in Areas Reporting Human Cases of Acute Encephalitis Syndrome in the Gorakhpur Region of Uttar Pradesh, India

Abstract: Outbreaks of acute encephalitis syndrome (AES) with high fatality and disability, are reported every year in the Gorakhpur region of Uttar Pradesh, India, with the etiology of >60% of the cases being attributed to scrub typhus. In the present study, the prevalence of Orientia tsutsugamushi, the etiological agent of scrub typhus, was investigated among animal hosts and their ectoparasitic trombiculid mites prevalent in AES-reported areas of Gorakhpur. A total of 154 rodents/shrews were collected using 777 Sherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Jain et al in a recent study from north India also reported a predominance of Gilliam-like strains (Jain et al, 2018b). Studies from small animals and mites from central India have also found that Karp and Gilliam predominate (Sadanandane et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…Jain et al in a recent study from north India also reported a predominance of Gilliam-like strains (Jain et al, 2018b). Studies from small animals and mites from central India have also found that Karp and Gilliam predominate (Sadanandane et al, 2018).…”
Section: Discussionmentioning
confidence: 88%
“…More than 80 per cent trapped shrew/rodent were infested with trombiculid mites, with Leptotrombidium deliense Walch as the predominant species. The overall chigger index, defined as the proportion of shrews/rodents having trombiculid mite infestation, was highest for S. murinus (21.3%) 18 .…”
Section: O Tsutsugamushi Infection In Small Animals and Mites (2015)mentioning
confidence: 97%
“…Although the clinical and laboratory findings among AES and AFI patients indicated the role of O. tsutsugamushi infection, evidence of the presence of the pathogen in animal hosts and vector mites was considered confirmatory to its transmission to humans. A cross-sectional survey of trombiculid mites was carried out during July and October 2015, in randomly selected villages in Gorakhpur with recent report of AES cases 18 . In the selected villages Sherman live traps were set in peri-domestic areas to catch rodents/shrews.…”
Section: O Tsutsugamushi Infection In Small Animals and Mites (2015)mentioning
confidence: 99%
See 2 more Smart Citations